(untitled) ([s.l], 1997)
A wide range of techniques is now available for analyzing protein primary structure. This program begins with the Edman degradation method for chemically sequencing proteins. Newer techniques based on gene sequence, DNA libraries, and complementary DNA probes, offer an alternative approach that complements the strengths of direct sequencing techniques. Mass spectrometry can confirm a sequence analysis by measuring the molecular weight of a protein with an error of only a few daltons
Keywords: Proteins,protein engineering,Amino acid sequence; Analysis